1994
DOI: 10.1007/bf03259387
|View full text |Cite
|
Sign up to set email alerts
|

A Formal Semantics of Data Flow Diagrams

Abstract: This paper presents a formal semantics of data flow diagrams as used in Structured Analysis, based on an abstract model for data flow transformations. The semantics consists of a collection of VDM functions, transforming an abstract syntax representation of a data flow diagram into an abstract syntax representation of a VDM specification. Since this transformation is executable, it becomes possible to provide a software analyst/designer with two ‘views’ of the system being modelled: a graphical view in terms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Other graphical notation communities have found that a formal semantics contributes to a solution, see [7,11] and papers in [3] for examples. The semantics presented in this paper could serve this purpose for Problem Frames.…”
Section: Introductionmentioning
confidence: 99%
“…Other graphical notation communities have found that a formal semantics contributes to a solution, see [7,11] and papers in [3] for examples. The semantics presented in this paper could serve this purpose for Problem Frames.…”
Section: Introductionmentioning
confidence: 99%
“…If not, the abstract problem model and the methods can be changed until the solution meets the specifications. Formal declarations such as Z are distinguished from less formal notations such as data flow diagrams [20] because they have a formal semantics that assigns a precise meaning to any formula in the declaration.…”
Section: Using Z Notation For Process Planningmentioning
confidence: 99%
“…Researchers have formalized DFDs [27,26] and attempted reverse engineering DFDs from code [6]. Liu et al proposed Conditional Data Flow Diagrams (CDFDs) [29] to resolve many of the ambiguity problems in Yourdon's DFDs.…”
Section: Related Workmentioning
confidence: 99%